APLIKASI PENYALURAN BIBIT PERKEBUNAN BERBASIS WEB PADA DINAS PERKEBUNAN PROVINSI JAMBI: Jambi;Plantation; Supply; Seeds;Web. - Pariyadi, Pariyadi; Pangestu, Aji (JURNAL AKADEMIKA, 2021)
The Jambi Provincial Plantation Office supplies plantation seeds from franchises, the seeds distributed by the Jambi Provincial Plantation Office to farmer groups, namely oil palm, cinnamon, coffee, and coconut. In the system that is currently running, farmers who will submit requests for seedlings come directly to the Jambi Provincial Plantation Office to collect application letters and statement letters. farmers fill out the form and then give it back to the Plantation Service along with the requirements. If these requirements are complete, the Plantation Service will provide information to farmers to collect seeds. Information at the Jambi Provincial Plantation Office is very much needed to assist employees and heads of offices in making a policy. So it is necessary to build a way to use technology to overcome these problems, namely by building a web-based application for distributing plantation seedlings. The web platform was chosen because it can be accessed easily from various devices. Input data consists of employee data, seed data, farmer group data, farmer data, seed application data, activity data, and news. The resulting output is a report on the distribution of seeds and a report on farmer group data. This application is expected to be used by the Jambi Provincial Plantation Office to make it easier for farmer groups to receive aid for oil palm, cinnamon, coffee, and coconut seeds more efficiently.